Pengembangan Instrumen Penilaian “HOTS” Dari Buku Tematik dengan Menggunakan QUIZIZZ di Sekolah Dasar - agus esti setiani (el-Ibtidaiy:Journal of Primary Education, 2022)
This research is motivated by the importance of developing HOTS-oriented assessments, especially on the dimensions of analyze (C4) and evaluate (C5) thinking processes in 21st century learning. The purpose of this study is to(1)explains the process of developing the "HOTS"-oriented assessment instrument from the thematic book using the Quizizz application in the fourth grade of elementary school,(2)verification the quality of the “HOTS”-oriented assessment instrument from thematic books using the Quizizz application in grade IV Elementary School,(3)verification responses from teacher and student's on the "HOTS"-oriented assessment instrument from the thematic book using the Quizizz application in the fourth grade of elementary school. This research design uses the ADDIE model. Data analysis in this research are descriptive qualitative and descriptive quantitative. The results showed that the quality of the developed product obtained a content validity assessment with a high category from material experts, the reliability of the questions was low, the level of difficulty included 2 difficult questions, 8 medium questions, and 10 easy questions, and had different questions. Based on the results of field trials, a "very positive" response was obtained from teacher and students in using the Quizizz Application for assessment.